The Scholarly Program of M. I. Rostovtzeﬀ - Gavrilov, Alexander K. (Hyperboreus, 2021)
The author asks: what was the place of philology in the stupendous historical work of M. Rostovtzeﬀ, considering that the great scholar identiﬁed his scholarly program with history and/or with the archaeology of the ancient world, leaving philology in their shadow. Such a disposition seems to reﬂect an ever-growing division and even a gap between those three disciplines as diﬀerent parts of ancient studies in the 20th century: natural from the point of view of specialized knowledge, it is fatal from the perspective of hermeneutics, where parts and the whole check each other in a very sophisticated way. Hence, the lecturer’s attempt to ask what the message of Rostovtzeﬀ’s work is on this question, since his teaching in the famous Nickolas Gymnasium in Tsarskoje Selo, along with its brilliant scholarly crew, already speaks for the presence of traditional philological values. The same is indicated by the commented and illustrated edition of Julius Caesar De bello Gallico for Russian gymnasia, philology being supplemented here by historical explanations, tables, and pictures. Also signiﬁcant was that Rostovtzeﬀ’s favorite auxiliary disciplines were epigraphy and papyrology, which, treating new and often hardly readable texts, already presuppose especially strong philological skills. Rostovtzeﬀ’s sensitivity to the artistic value of ancient literature is seen from his biography, which relates how he met and admired the literary persons of the Russian Silver Age and how he wrote lucid Russian himself. As for Rostvtzeﬀ’s lack of sympathy with exclusively philological topics, we guess that this was a consequence of the monotonous accent on grammatical competence disproportionately cultivated in the “classical” reforms of Count D. A. Tolstoy.